Soft Actuators Materials, Modeling, Applications, and Future Perspectives - Asaka, Kinji; Okuzaki, Hidenori (Springer Japan : Imprint: Springer, 2014)
The subject of this book is the current comprehensive research and development of soft actuators, and encompasses interdisciplinary studies of materials science, mechanics, electronics, robotics, and bioscience. As an example, the book includes current research on actuators based on biomaterials to provide future perspectives for artificial muscle technology. Readers can obtain detailed, useful information about materials, methods of synthesis, fabrication, and measurements. The topics covered here not only promote further research and development of soft actuators, but also lead the way to their utilization and industrialization. One outstanding feature of the book is that it contains many color figures, diagrams, and photographs clearly describing the mechanism, apparatus, and motion of soft actuators. The chapter on modeling is conducive to more extensive design work in materials and devices and is especially useful in the development of practical applications. Readers can acquire the newest technology and information about the basic science and practical applications of flexible, lightweight, and noiseless soft actuators, which are quite unlike conventional mechanical engines and electric motors. The new ideas offered in this volume will provide inspiration and encouragement to researchers and developers as they explore new fields of applications for soft actuators.